Diphtheria Incidence is a Public Health Challenge in Low- and Middle-Income Countries (LMICs) - Dwi Hartanti, Monica; Sari Dewi Panjaitan, Novaria; Hidayat, Syarif; Fitriana, Fitriana; Sunarno, Sunarno; Susanty, Sri (YCAB Publisher, 2025)
Background: Diphtheria remains a persistent public health issue, especially in low- and middle-income countries (LMICs), where vaccination coverage is often inadequate. Recent outbreaks, such as those in the 1990s, highlight the ongoing threat posed by this vaccine-preventable disease. The World Health Organization (WHO) provides data for monitoring the global trends in diphtheria cases, helping countries remain vigilant against its resurgence. Objective: This study aims to analyze the trend of diphtheria cases and incidence rates in 10 countries with the highest disease burden as a public health challenge in Low- and Middle-Income Countries (LMIC), with a focus on the impact of vaccination coverage. Methods: Longitudinal study was utilized in this research. G-power was performed to calculate the sample size. In accordance with the goal year that was being investigated, the research ranked the nations that were chosen into the top ten countries that had the largest number of cases of diphtheria. Our analysis was based on secondary data obtained from the WHO and included the years 2017 through 2021. In order to assess the distribution of healthcare access and vaccine coverage, we conducted a descriptive analysis of all of the data. This served the purpose of identifying significant public health concerns that contribute to diphtheria epidemics. We used the Stata 16 application to perform analysis on all of the data. Results: The majority of diphtheria cases occur in African and Asian countries, especially in areas with lower DTP-3 vaccination coverage. Yemen, Ethiopia, and Nigeria have high diphtheria rates due to disparities in access to health services and immunization programs. Countries with higher vaccination rates, such as India and Indonesia, report lower rates despite having high numbers of cases. This suggests that strong immunization programs are essential to control the disease. Conclusion: Diphtheria continues to be a significant public health challenge in LMICs, exacerbated by geographic and socioeconomic disparities in vaccination coverage. Global cooperation, including support from high-income countries, is essential to strengthen immunization programs and prevent future outbreaks. Diphtheria should be recognized as a global health threat, requiring comprehensive and coordinated efforts to achieve eradication. Keywords: Diphtheria; incidence rate; reported cases; vaccinated